2015
DOI: 10.3389/fnhum.2015.00031
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EEG-resting state independent networks by eLORETA-ICA method

Abstract: Recent functional magnetic resonance imaging (fMRI) studies have shown that functional networks can be extracted even from resting state data, the so called “Resting State independent Networks” (RS-independent-Ns) by applying independent component analysis (ICA). However, compared to fMRI, electroencephalography (EEG) and magnetoencephalography (MEG) have much higher temporal resolution and provide a direct estimation of cortical activity. To date, MEG studies have applied ICA for separate frequency bands only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 96 publications
1
121
0
Order By: Relevance
“…Exact low-resolution brain electromagnetic tomography (eLORETA) is a linear inverse solution that reconstructs cortical electrical activity from the scalp EEG data with correct localization [19-23]. Thus, eLORETA with EEG data has been widely used in neuroscience research [19, 20, 24-26]. Recent studies on cortical activity using fMRI or eLORETA have revealed that cortical sources work together in distant regions even in the resting state and construct a set of resting state networks (RSNs), which subserve specific brain functions [20, 27-30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exact low-resolution brain electromagnetic tomography (eLORETA) is a linear inverse solution that reconstructs cortical electrical activity from the scalp EEG data with correct localization [19-23]. Thus, eLORETA with EEG data has been widely used in neuroscience research [19, 20, 24-26]. Recent studies on cortical activity using fMRI or eLORETA have revealed that cortical sources work together in distant regions even in the resting state and construct a set of resting state networks (RSNs), which subserve specific brain functions [20, 27-30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, eLORETA with EEG data has been widely used in neuroscience research [19, 20, 24-26]. Recent studies on cortical activity using fMRI or eLORETA have revealed that cortical sources work together in distant regions even in the resting state and construct a set of resting state networks (RSNs), which subserve specific brain functions [20, 27-30]. In DLB, fMRI studies have reported that spatial configuration of RSNs was preserved but some activities of RSNs changed compared to healthy subjects [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…technique that allows the identification of intracerebral networks on the basis of scalp EEG measures [19]. The advantage of this technique is that the identified networks are represented across the different frequency bands.…”
Section: Independent Functional Network and Music Listening Jäncke Amentioning
confidence: 99%
“…The 'networks' we have identified are brain areas, which conjointly are activated and/or deactivated. In the following we describe and paraphrase the sLORETAfunctional independent component analysis (fICA) method according to the description given in the paper of Aoki et al [19]. The EEG recordings of each participant are first transformed to the frequency domain, resulting in a set of cross-spectral EEG matrices, for each frequency band and for each condition.…”
Section: Sloreta Analysismentioning
confidence: 99%
See 1 more Smart Citation